Analisis Pendukung Keputusan Pemilihan Benih Tomat untuk Pertanian Perkotaan Menggunakan Analytical Hierarcy Process (AHP) - Dinda Helma Saputry; Wahyuni, Rossi Septy (Universitas Putra Indonesia YPTK Padang, 2024)
Cultivating tomatoes for urban agriculture is one way to minimize product damage and accelerate the availability of tomatoes on a household scale. Limited land in urban agriculture makes a decision support analysis in choosing tomato seeds that are suitable for land conditions. The purpose of this study was to determine the criteria and alternatives for tomato seeds that are suitable for urban farming using the Analytical Hierarchy Process (AHP) method. The research was conducted from May to July 2023 with 100 respondents. The results of the instrument test show that the alternative funding criterion instruments used are valid and reliable. The priority levels of criteria generated from AHP are yield potential per hectare (0.231), number of viable fruit per plant (0.205), harvest age (0.174), weight per fruit (0.164), type of seed production (0.092), ripe fruit color (0.086) and plant height (0.049). Alternative seeds supported by AHP in choosing tomato seeds for urban agriculture are GBU tomatoes (0.418). The second and third alternatives are Hibrid (0.417) and GM (0.164).